Optimization of the size of UPQC system based on data-driven control design - Ye, Jian (2019)
The unified power quality conditioner (UPQC) has become the most attractive solution to improve the power quality (PQ) in the microgrids. However, the high manufacturing cost is a huge challenge of popularizing the UPQC system. This paper investigates the optimal size of the UPQC system based on the compensation requirements. A generalized strategy is proposed to optimize the size of the UPQC system, which determines the fundamental ratings of the shunt converter, series converter, and series transformer. A data-driven control (DDC)-based controller is developed using the variable phase angle control method to realize the implementation of the designed UPQC system under the different compensating conditions. Moreover, the MATLAB and OPAL-RT simulation results validate the practicability of the generalized strategy and the DDC-based controller.